FRAMING ANALYSIS OF CHINA'S RELATIONSHIP ABOUT THE SOUTH CHINA SEA DISPUTE ON CHANNEL NEWS ASIA - Daniel Susilo; Carl C.G. Dizon (Publikasi Indonesia, 2023)
Channel News Asia has been an excellent news site in Asia and other foreign countries because of its exceptional phrase complexity and informative text which is at par to The Guardian or VICE, despite being CNN tier news site by the web and operational design. Currently, the South China Sea conflict is part of the CNA’s subtle information delivery regarding UC-China rivalry without sounding like Yellow Journalism. Using Robert N. Entman’s framing analysis, the author was able to discover how CNA delivers the geopolitical issues to provide information regarding US-China rivalry in trade market.